Gothic visions of capitalism in a marxist tone Visions gothiques du capitalisme sur un ton marxiste (Quaestiones Disputatae: temas en debate, 2020)
In this text we want to show the contribution that Marx makes to the use of the gothic literary genre. In addition, other authors are presented who emphasized this use, giving it connotations that portray the present time according to the order of a novel in which the powers grouped by man, but beyond his control, turn the subsistence of human beings into something alienated and evil, zombie. Marx's explosive charge, then, is totally current, since it is seen from the Capital itself, or already, from the epigones of the Rhenish thinker.
Keywords: Capitalism; exploitation; alienation; fetishism; merchandise; gothic novel; vampirism; precariousness; use value; exchange value